The Impact of Implementing Corporate Social Responsibility(CSR) on Company Financial Performance - Divara, Sylvanda Aprilia; Rohman , Rizal Arsy Asy; Hwihanus, Hwihanus (CV. Lenggogeni Data Publishing, 2024)
Study This aim For know impact application of Corporate Social Responsibility (CSR) to the Company's Financial Performance by method compare or use meta- analysis method from a number of journal international with topic The impact of Corporate Social Responsibility(CSR) on Financial Performance . The results we got from journals the there is difference results or opinion as well as variables used , there are positive , negative correlation​ or No There is correlation about impact Corporate Social Responsibility(CSR) to performance finance . Corporate Social Responsibility itself that is form not quite enough answer company to environment social must​ carried out by the company , meanwhile performance finance is a description of the condition finance company or ability company in manage finance company .